1986
DOI: 10.1148/radiology.159.1.3513251
|View full text |Cite
|
Sign up to set email alerts
|

Breast lesions: differential diagnosis using digital subtraction angiography.

Abstract: To evaluate its potential for differentiating benign from malignant breast lesions, digital subtraction angiography of the breast (DSAB) was performed in 23 women with mammographic evidence of disease, and the results were compared with surgical biopsy findings. The DSAB technique employed breast immobilization with modest compression and bolus injection; following the injection of contrast material, 30-40 sequential subtraction images were obtained over a 5-minute interval. The average technical settings were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0
3

Year Published

1989
1989
2021
2021

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 0 publications
1
23
0
3
Order By: Relevance
“…When it is indicated, angiography can frequently indicate malignancy by showing the neovascularity of a tumor. However, angiographic examination of breast cancer has gained little attention, although previous studies have shown that breast tumor vessels display characteristics that suggest malignancy [2,3]. Continuous-wave Doppler sonography is another technique to detect the blood flow in breast tumors [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…When it is indicated, angiography can frequently indicate malignancy by showing the neovascularity of a tumor. However, angiographic examination of breast cancer has gained little attention, although previous studies have shown that breast tumor vessels display characteristics that suggest malignancy [2,3]. Continuous-wave Doppler sonography is another technique to detect the blood flow in breast tumors [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Angiogenesis leads to a higher vascularization and to an increased blood flow. Pre vious work in angiography and digital subtraction angiography of breast carcinoma had demonstrated that vascular abnormal ities are associated with malignant breast lesions [12,13]. The first studies on flow detection with Doppler ultrasound using the continuous-wave Doppler (CW Doppler) were described by Wells et al [14] and White and Cledgett [15].…”
Section: Discussionmentioning
confidence: 99%
“…Watt et al (16,17) and Ackerman et al (18) performed digital subtraction angiography of the breast, using an x-ray image intensifier in a conventional angiography system. They were able to demonstrate that benign and malignant lesions could be differentiated according to the strength of enhancement (referred to as "blush").…”
Section: Temporal Subtraction Angiographymentioning
confidence: 99%
“…Watt et al (16,17) and Ackerman et al (18) used temporal subtraction to depict the contrast enhancement. This technique, illustrated in Figure 1a, is analogous to the vast majority of digital subtraction angiography performed today.…”
Section: Temporal Subtraction Angiographymentioning
confidence: 99%
See 1 more Smart Citation